Analisis Faktor Faktor Yang Berpengaruh Terhadap Pendapatan Asli Daerah (PAD) Kota Denpasar - Jaya, Gde Bhaskara Perwira; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 5, Mei 2014 (pp.173- 226), 2014)
The aim of this study is to find out either or not PDRB, population, and the number of tourists influence the PAD in Denpasar. The data of this study is secondary. The analysis is using multiple linear regression. The analysis resulted that PDRB, population, and number of tourist simultaneously and significantly influence the actual local revenue in Denpasar in 1997-2011. The variance of the influence of PDRB, population, and number of tourists to the actual local revenue Denpasar showed by R Square = 0,896 which means that 89,6% of test result is explained by variables in the study while the rest of 13,1% is explained by other variables outside the study. Partially the number of tourists doesn't influece the PAD, while PDRB influences the PAD both positively and significantly. The population in this study influences negatively and significantly to PAD Denpasar. Therefore by intensifying the surveillance of taxpayers to all residents in productive age, it will be able to increase the PAD.
Keywords: PAD , PDRB , population , number of tourist